Confined Catalytic Janus Swimmers in a Crowded Channel: Geometry‐Driven Rectification Transients and Directional Locking. Issue 42 (15th September 2016) - Yu, Hailing; Kopach, Andrii; Misko, Vyacheslav R.; Vasylenko, Anna A.; Makarov, Denys; Marchesoni, Fabio; Nori, Franco; Baraban, Larysa; Cuniberti, Gianaurelio
Abstract : Self‐propelled Janus particles, acting as microscopic vehicles, have the potential to perform complex tasks on a microscopic scale, suitable, e.g., for environmental applications, on‐chip chemical information processing, or in vivo drug delivery. Development of these smart nanodevices requires a better understanding of how synthetic swimmers move in crowded and confined environments that mimic actual biosystems, e.g., network of blood vessels. Here, the dynamics of self‐propelled Janus particles interacting with catalytically passive silica beads in a narrow channel is studied both experimentally and through numerical simulations. Upon varying the area density of the silica beads and the width of the channel, active transport reveals a number of intriguing properties, which range from distinct bulk and boundary‐free diffusivity at low densities, to directional "locking" and channel "unclogging" at higher densities, whereby a Janus swimmer is capable of transporting large clusters of passive particles. Abstract : Combining catalytic Janus swimmers and passive beads in narrow channels, a number of intriguing dynamic properties are observed, ranging from distinct bulk and boundary‐free diffusivity at low densities to directional "locking" and channel "unclogging" at higher densities, whereby a Janus swimmer transports large clusters of passive particles.